2011
DOI: 10.1002/pa.385
|View full text |Cite
|
Sign up to set email alerts
|

Squawking, tweeting, cooing, and hooting: analyzing the communication patterns of government agencies on Twitter

Abstract: Twitter is rapidly gaining attention from strategic communicators for its ability to enhance communication campaigns. Whether using the site to augment word-of-mouth marketing campaigns or engage in conversations with stakeholders, Twitter has become the leading online social media outlet for marketing and public relations efforts. However, despite the service's ability to provide a forum for interacting with stakeholders, the site primarily began as a way for its users to provide one-way updates and dissemina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 42 publications
(53 reference statements)
6
122
1
8
Order By: Relevance
“…product-or service-related), rather than emotional or experiential, in appeal. Despite the much lauded relational benefits of social media, therefore, there is considerable evidence to suggest that many organisations and brands are posting more informational and one-way communications (Mamic and Alvaraz, 2013;Svensson et al, 2015;Waters and Jamal 2011;Waters and Williams 2011).…”
Section: Rq1: What Sponsorship-linked Twitter Content Is Produced By mentioning
confidence: 99%
“…product-or service-related), rather than emotional or experiential, in appeal. Despite the much lauded relational benefits of social media, therefore, there is considerable evidence to suggest that many organisations and brands are posting more informational and one-way communications (Mamic and Alvaraz, 2013;Svensson et al, 2015;Waters and Jamal 2011;Waters and Williams 2011).…”
Section: Rq1: What Sponsorship-linked Twitter Content Is Produced By mentioning
confidence: 99%
“…Although many companies have a poor record for engaging with individual social media users (Waters & Williams, 2011), companies should respond to user comments from an interactivity standpoint. According to the classic contingency viewpoint of interactivity, there are three levels of interactivity: non-interactive, reactive, and interactive (Rafaeli, 1988;Sundar, Brwon, & Kalyanaraman, 2003).…”
Section: Should Companies Respond To Individual Users On Twitter?mentioning
confidence: 99%
“…These studies are also based on analysing observed practice and interviews. The Walters and Williams [8] research analysed actual tweets to establish if the information was mainly one or two way communication. Their results showed the majority of information was only one way as government tends to redirect questions to other sites showing a lack of communication.…”
Section: Current Research In Community Participation With Ictmentioning
confidence: 99%